2018
DOI: 10.1590/s1980-657420180003e0046-18
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multicomponent intervention on the screen time of Brazilian adolescents: non-randomized controlled study

Abstract: The aim of this study was to verify the effectiveness of a multicomponent, school-based intervention in reducing screentime in adolescents according to sex. Methods: This is a non-randomized controlled intervention study focusing on cardiorespiratory fitness, body image, nutrition and physical activity. Screentime (television, computer/ video game) was the secondary outcome of the intervention and was addressed using educational strategies (folders, posters, educational sessions and group discussions). Screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…The results obtained are consistent with the research results provided by other authors who revealed a reverse relationship between physical activity and physical fitness in conformity with the total time of using digital technologies [7,[13][14][15][16]18].…”
Section: Shs Web Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained are consistent with the research results provided by other authors who revealed a reverse relationship between physical activity and physical fitness in conformity with the total time of using digital technologies [7,[13][14][15][16]18].…”
Section: Shs Web Ofsupporting
confidence: 92%
“…Currently, there is an increasing number of scientific works concerned with the analysis of the relationship between the intensive use of digital technologies by children in everyday life and the functional state of the body [5][6][7][8][9][10][11][12], physical activity and motor fitness [6,7,[13][14][15][16][17][18]. Despite the available data, there are some unsolved issues associated with assessing the impact of digital technologies on the health and functional state of children at various stages of ontogenesis with due regard to the development of motor abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions in both children and adolescents resulted in changes in the school environment; however, with children, interventions were focused on sports materials (ropes, ball, bows, cone, mat, tape and rubber bands, and track designed with colors) [56,59,66,68,76]. Interventions with adolescents focused on access to booklets, pamphlets, posters, banners, and exercise guides [19,20,[22][23][24][25][26][28][29][30][31][32][33][34][35][36][44][45][46][47][48][49]51,78]. Only adolescents had the opportunity to interact electronically with instructional SMS for PA practice with motivational messages about environmental changes and access to information on healthy eating habits and creation of an electronic diary of PA and food [20,[28][29][30][31][32][33][44][45][46][47][48][49]67].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarizes the PL investigated in the studies according to age group. The components most frequently evaluated in interventions were PA attributes [18][19][20][21][23][24][25][26][27][28][29][30][31][32]37,41,42,44,45,48,50,[52][53][54][56][57][58][59][61][62][63][64][65][66][67][68][69][70][71][72]75,76] (30 studies; 71.4%). In general, children were evaluated in terms of fine and global motor skills, balance, body schema, and spatial and temporal organization [50,56,76,80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation